ENDURING HARM: Unlikely Comparisons, Slow Violence and the Administration of Urban Injustice. (23rd August 2022) - Anand, Nikhil; Wiggin, Bethany; Kamath, Lalitha; Deekshit, Pranjal
Abstract: In this comparative and collaborative collection of essays we work through contemporary and historical practices of governing urban waters in Philadelphia and Mumbai. Taken together, the essays in this collection argue that events of enduring harm visited upon racialized, marginalized citizens are produced through slow bureaucratic processes of aversion, ambiguation and ambivalence, perpetuated in and through regulatory regimes, water quality standards, legal discourses and everyday practices in the city. These practices entangle racialized and poorer populations in situations of durable and everyday harm and are central to the creation, maintenance and reproduction of vulnerable and disposable human and non‐human life in the city.